Chemopreventive effect of a novel oleanane triterpenoid in a chemically induced rodent model of breast cancer. Issue 5 (29th March 2013) - Bishayee, Anupam; Mandal, Animesh; Thoppil, Roslin J.; Darvesh, Altaf S.; Bhatia, Deepak
<x xml:space="preserve">Abstract</x> Breast cancer represents one of the most frequently diagnosed cancers and predominant causes of death in women worldwide. The value of preventive therapy to limit the devastating impact of breast cancer is well established. Various plant triterpenoids and their synthetic analogs have shown significant promise as potent chemopreventive agents in breast cancer. The current study was initiated to investigate mechanism‐based chemopreventive potential of a novel synthetic oleanane triterpenoid (methyl‐25‐hydroxy‐3‐oxoolean‐12‐en‐28‐oate, AMR‐Me) against 7, 12‐dimethylbenz(a)anthracene (DMBA)‐initiated rat mammary carcinogenesis, an experimental rodent tumor model that closely resembles human mammary cancer. Rats were orally administered with AMR‐Me (0.8, 1.2 and 1.6 mg/kg) three times per week for 18 weeks. Following two weeks of AMR‐Me treatment, mammary carcinogenesis was initiated by oral administration of DMBA (50 mg/kg body weight). At the end of the study (16 weeks following DMBA exposure), AMR‐Me exhibited a striking inhibition of DMBA‐induced mammary tumor incidence, total tumor burden, average tumor weight and reversed histopathological alterations without toxicity. AMR‐Me dose‐dependently suppressed abnormal cell proliferation, induced apoptosis, up‐regulated pro‐apoptotic protein Bax and down‐regulated antiapoptotic protein Bcl‐2 in mammary tumors. AMR‐Me upregulated the transcriptional levels of Bax, Bad, caspase‐3, caspase‐7 and poly(ADP‐ribose) polymerase and down‐regulated Bcl‐2. These results clearly demonstrate for the first time that novel triterpenoid AMR‐Me exerts chemopreventive efficacy in the classical DMBA model of breast cancer by suppressing abnormal cell proliferation and inducing apoptosis mediated through mitochondrial pro‐apoptotic mechanisms. AMR‐Me could be developed as a chemopreventive drug to reduce the risk of human breast cancer that remains a devastating disease.